The impact of digital transformation and industry 4.0 on the aspects of value: Evidence from a meta-synthesis - Cruzara, Giovani; Takahashi , Adriana Roseli Wunsch; Sandri, Emanuel Campigotto; Cherobim, Ana Paula Mussi Szabo (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
We use a meta-synthesis approach to review qualitative case studies where the relationship between value and digital transformation/industry 4.0 is explored. Our goal is to provide contributions beyond those achived on the original studies, thus providing novel insights from the study findings. The results demonstrate that value is explored on two dimensions: Business Models and value chains. However, we identify that studies tend to overlook critical points of industry 4.0 when exploring value. This meta-synthesis demonstrate that studies need to encompass a broader scenario, dealing also with co-creation of value and also considering ecosystem aspects where the organizations are inserted for the comprehension of value capture aspects. We conclude by providing future research directions based on the meta-analysis of the reviewed studies.